PENGARUH KEPEMILIKAN PUBLIK TERHADAP KETEPATAN WAKTU PENYAMPAIAN LAPORAN KEUANGAN DENGAN REPUTASI KAP SEBAGAI VARIABEL MODERASI - Nuh, Muhamad; Purwasih, Desy (Jurnal Revenue : Jurnal Ilmiah Akuntansi, 2023)
This study aims to determine the effect of public ownership on the timeliness of submission of financial statements with KAP reputation as a variable.Moderating in Sub-sector companiesProperty & Real Estate listed on the Indonesia Stock Exchange in 2017–2021. This type of research is to use a quantitative approach to research using techniquespurposive sampling namely a sample collection method based on considerations and criteria that are in accordance with the research objectives. The sample used was 160 data on 32 companies listed on the Indonesia Stock Exchange in 2017-2021. The analysis technique used for this test is logistic regression andModerated Regression Analysis (MRA) using the Eviews application version 9. Based on the results of this study it shows that Public Ownership has an effect on the Timeliness of Submission of Financial Statements, while KAP's Reputation does not moderate the Effect of Public Ownership on the Timeliness of Submission of Financial Statements